1980
DOI: 10.1107/s0021889880012009
|View full text |Cite
|
Sign up to set email alerts
|

Optical transforms of disordered molecular crystals

Abstract: An Optronics P‐1700 film‐writing device is used to produce simulations of disordered organic molecular crystals. The simulations may be used directly to obtain optical diffraction patterns for comparison with X‐ray diffuse scattering photographs of real crystals. Examples of some substituted anthracenes are given to demonstrate the diversity of disorder effects which may be included and the level of precision achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…This has been confirmed by two independent methods and is not an artifact of the refinement procedure. The X-ray diffuse scattering studies to be reported later (Welberry, 1980) show that, in addition to the preferred site occupancy determined here, the orientations of neighbouring molecules related by the statistical centre of symmetry are additionally correlated. In this way, we find that the Br/Me sites which are 6.2/k apart (see Fig.…”
Section: Discussionsupporting
confidence: 60%
“…This has been confirmed by two independent methods and is not an artifact of the refinement procedure. The X-ray diffuse scattering studies to be reported later (Welberry, 1980) show that, in addition to the preferred site occupancy determined here, the orientations of neighbouring molecules related by the statistical centre of symmetry are additionally correlated. In this way, we find that the Br/Me sites which are 6.2/k apart (see Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Multiple z-matrices were used, though they are essentially the same matrix with the CH 3 and Cl transposed. It has been shown that in CMA the two species (or flipped versions of the one species) occur in the ratio ∼69 : 31 [28][29][30].…”
Section: Preliminary Calculationsmentioning
confidence: 99%
“…Although it was necessary to use different crystals for each mounting and individual sections were recorded at various times over a period of several months, spherical solutiongrown (from PE) crystals of -0.5 mm diameter were used in each case. To aid in preliminary investigations and for later reference, these photographs were digitized and the data processed in the manner described by Welberry & Jones (1980) to produce the undistorted views of each reciprocal section which are shown in Fig. 2.…”
Section: Data Collectionmentioning
confidence: 99%